PEMAKAIAN KOMPOSISI PADA PEMBERITAAN KORAN MALUT POS EDISI NOVEMBER 2024 - Ahmad, Idrus; Boriri, Agus; Djais, Idwan (Jurnal Pendidikan dan Ekonomi (JUPEK), 2025)
This study aims to analyze and describe the use of composition in the news of the Malut Pos newspaper, November 2020 edition, including internal and external composition. Using a qualitative descriptive method, this study also explores the form of verbal compound words that are paired with nouns, adjectives, adverbs. And how the process of combining words and words, words and main words, or main words and main words cannot be separated from each other. The data source in this study is the Malut Pos newspaper, November 2024 edition. The reason for using the data from that edition of the newspaper is because in addition to the many uses of composition, the documents are also complete.